“Você quer me ouvir?” narrativas (auto)biográficas de professoras da rede municipal de Vitória/ES aposentadas por invalidez (décadas de 1980 a 2000) - Azevedo, Karla Veruska (2015)
The present study aimed at disclosing and investigating the narratives of teachers, retired due to disability, who worked with the early grades of the municipal elementary education network in the city of Vitória, Espírito Santo State, Brazil, between the decades of 1980 and 2000. With such an objective in mind, I sought to identify how the relationship of these teachers with the school environment and work production developed. It was initially hypothesized that the teachers‟ narratives would offer enough evidence to analyze “if” and “how” the health/illness, subordination/prestige, pleasure/suffering processes arise in the narratives, drawing on the portrayal of lived experiences and practices and on how these issues affected teachers as subjects and leads of such history. I tried to understand how these teachers evaluated their teaching activity in different historical moments and the relationship established with the education management models developed by the municipality in the observed period. The study relied on contributions from Abrahão, Catani, Josso, Pineau to discuss and support the option for an (auto)biographical line. The teachers‟ narratives raise questions that all levels of education professionals and managers should ponder, as they bring about aspects regarding their initial training and the history and politics of education in the city of Vitória, its pedagogical practices and relationship processes in the school environment that impact the work process.